2017
DOI: 10.5897/ajar2016.11365
|View full text |Cite
|
Sign up to set email alerts
|

Performance of cassava (Manihot esculanta. Cratz) clones in potential and low moisture stressed areas of Ethiopia

Abstract: and Kello (standard check) were evaluated by using randomized complete block design replicated three times. The evaluation was carried out for two consecutive years, from 2012 to 2014. The combined analysis result indicated that there was statistically significant difference among the clones tested and the locations where the experiment was conducted. The clone AWC-1 (37.17 t/ha) followed by AWC-2(35.52 t/ha) and AWC-5 (35.51 t/ha) gave the highest storage root yield but there was no statistically significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…World-wide, cassava is a staple food for more than 800 million people [4]. However, agronomic performance of cassava is increasingly constrained by the two principal biotic constraints, cassava mosaic disease (CMD), caused by cassava mosaic geminiviruses (CMGs) and cassava brown streak disease (CBSD), caused by cassava brown streak viruses (CBSVs) [3,[5][6][7]. In Africa, yields are only 8-10 tonnes per hectare, on average approximately half of those achieved in Asia and Latin America [8].…”
Section: Introductionmentioning
confidence: 99%
“…World-wide, cassava is a staple food for more than 800 million people [4]. However, agronomic performance of cassava is increasingly constrained by the two principal biotic constraints, cassava mosaic disease (CMD), caused by cassava mosaic geminiviruses (CMGs) and cassava brown streak disease (CBSD), caused by cassava brown streak viruses (CBSVs) [3,[5][6][7]. In Africa, yields are only 8-10 tonnes per hectare, on average approximately half of those achieved in Asia and Latin America [8].…”
Section: Introductionmentioning
confidence: 99%
“…The result of this study is similar with the report of [28] who reported cassava genotypes collected from southwest Ethiopia had significant difference in storage tuber yield and related traits. Similarly, [26] also reported high significant (p<0.01) difference among cassava genotypes tested at Hawassa, Amaro, Jima and Sekota areas of Ethiopia. The storage tuber length is also vary significantly (p<0.05) among tested cassava genotypes.…”
Section: Discussionmentioning
confidence: 79%
“…This result is supported by the report of [29], who reported the storage tuber length of cassava grown in clay soil and high moisture stress areas of southern Ethiopia are reduced significantly. Besides, [26] reported variety Kello produced longest mean storage tuber of 40.67 cm grown in major growing areas of Ethiopia. However, in this study the storage tuber length obtained from Jimma (48.90) and Metu (53.10 cm) is higher than the report of [26].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations